Microstructure evolution and dynamic softening mechanisms during high-temperature deformation of a precipitate hardening Ni-based superalloy. (September 2018) - Wan, Zhipeng; Hu, Lianxi; Sun, Yu; Wang, Tao; Li, Zhao
Abstract: Hot compression tests have been performed to study the microstructure evolution of as-forged precipitate hardening Ni-based superalloy in the temperature range 1060–1180 °C and strain rate range 0.001–10s −1 . The dynamic softening mechanisms and nucleation mechanisms of dynamic recrystallization of deformed specimen in both γ single and γ+γ′ phase region as well as a wide range of strain rates were discussed using electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) technique. The results suggest that discontinuous dynamic recrystallization (DDRX), characterized by grain boundary bulging, takes place under all studied deformation conditions in this alloy. At relatively high deformation temperatures and low strain rates, the process of dynamic softening, that is as a result of the continuous original boundary migration induced the increased grain size as well as decreased dislocation substructures and subgrain boundaries, is identified by microstructural observations. The DDRX is promoted when the strain rate is increased. At relatively low deformation temperatures, the movement and rearrangement of dislocations in original grains as well as the migration of DRX grain boundaries are hindered by the presence of γ′ precipitates, indicating that DDRX and particle-induced continuous dynamic recrystallization (PI-CDRX) can occur simultaneously. Highlights: Discontinuous dynamic recrystallization takes place under all studied deformation conditions in this alloy. Discontinuous dynamic recrystallization is suppressed at low strain rate and high temperature or low temperature. Continuous original boundary migration would impede the nucleation of dynamic recrystallization grains. A low temperature is needed for the occurrence of particle induced continuous dynamic recrystallization.